2019
DOI: 10.2147/ndt.s202329
|View full text |Cite
|
Sign up to set email alerts
|

<p>The level of IL-6 was associated with sleep disturbances in patients with major depressive disorder</p>

Abstract: Purpose: Major depression disorder (MDD) was associated with inflammatory processes, but association results of inflammatory syndrome and MDD were inconsistent. To provide more evidence, we measured the plasma levels of IL-1β, IL-6, interferon (INT)-α2, INT-γ, and tumor necrosis factor (TNF)-α in patients having MDD and explored correlations between the five proinflammatory cytokines and specific depressive symptoms. Patients and methods: Plasma concentrations of IL-1β, IL-6,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 35 publications
0
26
0
Order By: Relevance
“…This could be related to a natalizumab-induced decrease in inflammatory markers implicated in sleep disturbance, depression, and fatigue in both CSF and in plasma. [28][29][30][31][32][33] However, direct evidence linking the biological effects of natalizumab with its effect on these symptoms is lacking, and the contribution of these findings in defining the anecdotal "feelgood effect" of natalizumab needs to be further studied.…”
Section: Discussionmentioning
confidence: 99%
“…This could be related to a natalizumab-induced decrease in inflammatory markers implicated in sleep disturbance, depression, and fatigue in both CSF and in plasma. [28][29][30][31][32][33] However, direct evidence linking the biological effects of natalizumab with its effect on these symptoms is lacking, and the contribution of these findings in defining the anecdotal "feelgood effect" of natalizumab needs to be further studied.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep plays a vital role in regulating the body’s innate and adaptive immune responses, and poor sleep quality is associated with chronic inflammation. Several cytokines and chemokines, such as IL-1β, IL-6, TNF-α, and high-sensitivity CRP, are related to poor sleep quality [ 29 , 30 ]. A previous study reported that poor sleep quality is equivalent to insulin resistance and is a risk factor for metabolic and cardiovascular diseases [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have also revealed that patients with MDD have increased levels of plasma and serum concentrations of pro-inflammatory cytokines including IL-6 in comparison with healthy controls [24,100,115,116]. It should be noted that three meta-analyses verified increased peripheral IL-6 levels in MDD patients compared to healthy volunteers [38,116,117].…”
Section: On the Role Of Interleukin-6 In Depression Il-6 Alterations mentioning
confidence: 99%